PENGARUH MOTIVASI KERJA ISLAMI, LINGKUNGAN KERJA ISLAMI DAN KEPEMIMPINAN ISLAMI TERHADAP KINERJA KARYAWAN TOKO BASMALLAH CABANG TEMPUREJO JEMBER - Putri, Septi Lenita; Fatimah, Feti; Rusdiyanto, Rusdiyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
This research aims to test the partial influence of Islamic work promotion (X1), Islamic Workplace (X2) and Islamic Leadership (X3) on Employee Performance (Y) at the Basmallah Tempurejo Shop, Jember. The sample size is 75 employees. The questionnaire takes data from instruments (evidence and credibility tests), superior hypothesis testing (multicollinearity, normality and heteroscedasticity tests), multiple regression analysis and hypothesis testing (test and coefficient of determination). All of these methods are used with SPSS 21.0 support. The impact of the examination shows that the flexibility of Islamic activities (X1) has a relevant impact on employee abilities (Y) amounting to 0.026, the flexibility of Islamic activities (X2) has a relevant impact on employee capabilities (Y) amounting to 0.028 and the flexibility of Islamic leadership (the event proves that Islamic activity motivation, place Islamic work and Islamic leaders have an influence of 79% on employee job changes. Other factors not taken into account during this examination represent the remaining 0.21% or 21%.